Toll-like receptor 2 signaling pathway activation contributes to a highly efficient inflammatory response in Japanese encephalitis virus-infected mouse microglial cells by proteomics - Zhao, Guanyu; Gao, Yan; Zhang, Jiaqi; Zhang, He; Xie, Changzhan; Nan, Fulong; Feng, Sheng; Ha, Zhuo; Li, Chenghui; Zhu, Xiangyu; Li, Zhuoxin; Zhang, Ping; et al. (Frontiers in Microbiology, 2022)
Thousands of people die each year from Japanese encephalitis (JE) caused by the Japanese encephalitis virus (JEV), which is probably due to exacerbation of the inflammatory response that impairs the course of the disease. Microglia are mononuclear phagocytic cells located within the parenchyma of the central nervous system, which plays a key role in the innate immune response against JEV infections. However, the involvement of toll-like receptor 2(TLR2) in the inflammatory response during the early stages of JEV infection of BV2 cells was not clear. We then aimed to evaluate protein profiles and determine the role of TLR2 in the inflammatory response of JEV-infected BV2 cells. High depth tandem mass tags labelling for quantitative proteomics was used to assess JEV infected-BV2 cells and compared immune response profiles at 6 h, 12 h, and 24 h post-infection (hpi). 212 upregulated proteins were detected at 6 hpi, 754 at 12 h, and 191 at 24 h. According to GO and KEGG enrichment analysis, immune response-related proteins were enriched among the elevated proteins. A parallel reaction monitoring test, Western blot, and qPCR results showed that the adaptor protein MyD88 was not activated. Meanwhile, the expression of key proteins downstream MyD88 like IRAK1, IRAK4, and TRAF6 didn’t increase. However, the expression of PI3K-AKT increased. By inhibited key proteins, TLR2, PI3K, and AKT, we confirm that JEV activated TLR2, resulting in a robust inflammatory response. TLR2-PI3K-AKT signaling axis was shown to be critical in the early stages of the JEV infection-induced inflammatory response in microglia.